Ε constrained differential evolution for economic dispatch with valve-point effect. (1st January 2011) - Noman, Nasimul; Iba, Hitoshi
A novel and effective method for solving economic load dispatch (ELD) problem is presented in this work by integrating the ε constrained method with differential evolution (DE) algorithm. The ε constrained method sets us free from selecting the appropriate value for the penalty coefficient in the objective function, which is difficult and often chosen empirically. Differential evolution with ε constrained method ( ε DE) has proven to be effective in solving non-linear constrained optimisation problems. Here, the effectiveness of ε DE, in solving ELD problems is investigated by using three different ELD problems that take the valve-point loading effect into consideration. The proposed approach provides very high quality solutions which are very competitive to other existing techniques to ELD considering the valve-point effect.